Tinjauan Ketepatan Kode dengan Pending Klaim Pasien Rawat Inap BPJS Kesehatan di RSUD dr. Adnaan Wd Payakumbuh Tahun 2021 - Oktamianiza Oktamianiza; Isya Apda Reza; Dian Novita (Jurnal Rekam Medis dan Informasi Kesehatan, 2022)
The accuracy of the coding of a diagnosis is influenced by the clarity of writing and the completeness of the diagnosis. The right diagnosis will produce the right code data as well. If there is an error in coding, this will have an impact on claims for health care costs. This research was conducted at the Regional General Hospital dr. Adnaan WD Payakumbuh. This type of research is descriptive qualitative with in-depth interviews with the head of the medical record installation, inpatient coder, and case mix officers. The results showed that there were 3 human resources related to coding with educational qualifications of D3 Medical Record, coding SOPs and case mix SOPs already existed and had been implemented, the implementation of coding training was carried out, the implementation of the disease diagnosis code was still constrained because the resume did not match the status. , insufficient supporting data, and incorrect placement of primary and secondary diagnoses, it takes several days for the revision of pending claims to be carried out to the doctor in charge of the patient (DPJP). In addition, the coder still has difficulty in reading the doctor's diagnosis, thus affecting the quality of the code and having an impact on pending claims.